INCREASING THE EFFICIENCY OF INSTITUTIONAL INTERACTION DURING THE TRANSFER OF INNOVATIONS IN THE AGRO-INDUSTRIAL COMPLEX - Elena DERUNOVA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
In order to form a new model of economic growth that ensures food security and sustainability of the agro-food complex, it is necessary to improve the institutional conditions for the development of digital technologies and high-tech products in agricultural production. The purpose of the article is to develop theoretical and methodological aspects of the institutional interaction of participants in the innovation process, as well as to create mechanisms for systemic innovation mediation that stimulates innovation activity. The article develops conceptual provisions for regulating the development of institutional interaction, assesses the innovative activity of some European countries and assesses the dynamics of indicators of the volume of state support for the agro-industrial complex in 2013-2020. Measures are proposed to increase the efficiency of communication interaction between the participants of the innovation process using the mechanism of innovation system mediation. The practical value of the results lies in the possibility of forming an innovative development strategy in the context of the introduction of digital technologies and science-intensive products as a vector of sustainable socio-economic development of Russia.